Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fnins.2019.00836
|View full text |Cite
|
Sign up to set email alerts
|

Basilar Artery Tortuosity Is Associated With White Matter Hyperintensities by TIMP-1

Abstract: Background and Purpose To test the hypothesis that the imbalance between matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinases (TIMPs) may play a potential role in bridging vertebrobasilar dolichoectasia (VBD) with lacunar infarction (LI) and white matter hyperintensities (WMH). Methods We studied 212 patients with vertigo who underwent multimodal magnetic resonance imaging (MRI) tests for VBD, LI, and WMH identification. We investigated biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
(40 reference statements)
2
18
0
Order By: Relevance
“…Our results showed that the serum level of MMP-9 and the ratio of MMP-9/TIMP-1 levels were both significantly higher in vertigo patients with VBD and BA elongation compared to those with normal arterial size. 50 Our findings suggest MMP-9 and TIMP-1 may be involved in the pathogenesis of VBD and WMH, which may help with the diagnosis and treatment of these cerebrovascular diseases in the future. Overview of pathological mechanisms underlying the association between intracranial arterial dolichoectasia (IADE) and cerebral small vessel disease (CSVD).…”
Section: Matrix Metalloproteinasementioning
confidence: 64%
See 1 more Smart Citation
“…Our results showed that the serum level of MMP-9 and the ratio of MMP-9/TIMP-1 levels were both significantly higher in vertigo patients with VBD and BA elongation compared to those with normal arterial size. 50 Our findings suggest MMP-9 and TIMP-1 may be involved in the pathogenesis of VBD and WMH, which may help with the diagnosis and treatment of these cerebrovascular diseases in the future. Overview of pathological mechanisms underlying the association between intracranial arterial dolichoectasia (IADE) and cerebral small vessel disease (CSVD).…”
Section: Matrix Metalloproteinasementioning
confidence: 64%
“…We studied 212 patients with vertigo who underwent multimodal MRI tests for VBD, LI, and WMH identification. Our results showed that the serum level of MMP-9 and the ratio of MMP-9/TIMP-1 levels were both significantly higher in vertigo patients with VBD and BA elongation compared to those with normal arterial size [ 50 ]. Our findings suggest MMP-9 and TIMP-1 may be involved in the pathogenesis of VBD and WMH, which may help with the diagnosis and treatment of these cerebrovascular diseases in the future.…”
Section: Mechanisms Underlying the Association Between Iade And Csvdmentioning
confidence: 99%
“…Cerebral veins and CSF are also thought to be important compartments for compensating arterial pulse pressure (20). Second, we did not evaluate the MMP level, as a previous study suggested that MMP dysfunction could bridge large intracranial arterial outward remodeling and CSVD (21). Third, the measurement of intracranial artery calibers is affected by cardiac cycle and artery pulse and it might depend on the imaging time on MRA.…”
Section: Discussionmentioning
confidence: 99%
“…The curved segments of the BA were also taken into account. The BA actual length was measured along the centerline from the top of the BA to the junction of both VAs (18). The straightened length was measured by a linear distance between the top of the BA to the junction of both VAs (18).…”
Section: Mr Image Analysismentioning
confidence: 99%
“…The BA actual length was measured along the centerline from the top of the BA to the junction of both VAs (18). The straightened length was measured by a linear distance between the top of the BA to the junction of both VAs (18). The tortuosity of the BA was measured by the following formula (18): tortuosity = (actual length/ straightened length − 1) × 100.…”
Section: Mr Image Analysismentioning
confidence: 99%